2000
DOI: 10.1021/cm0000907
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2 Hollow-Fibers Using Supramolecular Assemblies

Abstract: trans-(1R,2R)-1,2-Cyclohexanedi(11-aminocarbonylundecylpyridinium) hexafluorophosphate (1) was synthesized. The sol−gel polymerization of Ti[OCH(CH3)2]4 using compound 1 as a self-assembled template afforded fibrous TiO2 materials with a “macaroni”-like structure. The unique structure of TiO2 could be created by the formation of a fibrous self-assembled aggregate and electrostatic interaction between anionic titania species and cationic 1 under basic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(181 citation statements)
references
References 26 publications
(16 reference statements)
5
167
0
6
Order By: Relevance
“…As can be seen from this image, hollow TiO 2 nanofibers (TiO 2 nanotubes: outer diameter, ca.440 nm, inner diameter, ca.270 nm) were formed. The nanotubes obtained are seemed to have a uniform diameter as compared to the diameter range reported by Kobayashi et al (Kobayashi et al, 2000). We determined that a precursor nanofiber with a skin-core structure would be obtained by our method; the skin layer is a PVA-TTIP hybrid, and the core is pure PVA.…”
Section: Apparatus and Proceduressupporting
confidence: 59%
See 1 more Smart Citation
“…As can be seen from this image, hollow TiO 2 nanofibers (TiO 2 nanotubes: outer diameter, ca.440 nm, inner diameter, ca.270 nm) were formed. The nanotubes obtained are seemed to have a uniform diameter as compared to the diameter range reported by Kobayashi et al (Kobayashi et al, 2000). We determined that a precursor nanofiber with a skin-core structure would be obtained by our method; the skin layer is a PVA-TTIP hybrid, and the core is pure PVA.…”
Section: Apparatus and Proceduressupporting
confidence: 59%
“…Kobayashi et al reported the preparation of TiO 2 nanotubes using the gelation (self-assembly with a rodlike fibrous structure) of an organogelator (It is not ES.) (Kobayashi et al, 2000(Kobayashi et al, , 2002. The organogelator is a cyclohexane derivative that was specially synthesized by this research group.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysts can also be deployed as a fixed matrix, usually as a film or in the form of nano tubes/rods. Preparation of these materials, however often requires convoluted and cost-intensive manufacturing processes, and they also have a reduced reactive surface area compared to powder and pelletised materials [11,14]. A novel approach for deploying photocatalysts is annealing the materials to hollow, buoyant glass spheres.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are strongly related to the synthesis processes. Numerous solution techniques, for example, sol-gel, emulsion, colloidal, and aerosol processes, have been used to synthesize a variety of nanoparticles [2][3][4][5][6]. As an alternative approach, the electrochemical route is of considerable interest because of a possibly precise particle size control achieved by adjusting current density or applied potential.…”
Section: Introductionmentioning
confidence: 99%